Feminizing functioning ovarian tumors - Samame Boggio, Guido (2015)
I have presented a statistical study of the Pavilion No. 5, 2nd. Hall, performed in 32 years; having found ginecópatas 15.480, of which 1,480 had ovarian tumors; of these, two had tumors teak and 9 to tumors of granulosa cells. The frequency of ovarian tumors was 9.2% of tumors and granulosa cells to 0.62% and 0.13% of tumors of the teak. Regarding age, we must say that 60% were active genital age and other menopause. In relation to malignancy, we must say that most of them did not present further complications; however, a patient of 15 years metastasized quickly, dying within 3 months after the operation; in other 3 metastases they occurred after 4 years of evolution. In relation to treatment is surgical say that we will be conservative in young patients who have had no family and taking them into periodic inspection.